Critical appraisal of intra-articular glucocorticoid injections for symptomatic osteoarthritis of the knee. Issue 1 (January 2021) - Samuels, J.; Pillinger, M.H.; Jevsevar, D.; Felson, D.; Simon, L.S.
Summary: Objective: Intra-articular (IA) injections of glucocorticoids (GCs) have been shown to decrease pain, increase mobility, and improve quality of life in patients with osteoarthritis (OA) of the knee. Concerns about cartilage loss with IA GCs have prompted reconsideration of their use in knee OA. This review has three objectives: 1) critically review the clinical, molecular, and structural effects of IA GCs in knee OA; 2) provide a design for a clinical trial aimed at improving our understanding of the long-term consequences of IA GCs; and 3) provide practical guidance on the use of IA GCs in patients with knee OA based on current information. Design: A narrative review of current literature on the use of IA GCs for OA of the knee. Results: Important questions remain to be fully answered with respect to IA GCs, including long-term effects on all aspects of the structural and molecular environment of the knee, and identification of factors that can reliably predict a positive or negative response to IA GCs. Conclusions: While awaiting results from an appropriately designed study, several provisional statements regarding IA GCs can be put forward: 1) IA GCs appear to be a relatively safe option that is effective in specific patients with symptomatic knee OA; 2) there is no definitive evidence that IA GCs accelerate joint deterioration to an important extent or hastens the requirement for knee replacement; and 3) there are few contraindications to IA GCs and injection-associated complications are rare when IA GCs are delivered with proper technique.